2020
DOI: 10.1002/jgh3.12336
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors, and racial and ethnic differences in hepatocellular carcinoma

Abstract: Despite improved screening and surveillance guidelines, significant race/ethnicity‐specific disparities in hepatocellular carcinoma (HCC) continue to exist and disproportionately affect minority and disadvantaged populations. This trend indicates that social determinants, genetic, and environmental factors are driving the epidemic at the population level. Race and geography had independent associations with risk of mortality among patients with HCC. The present review discusses the risk factors and issues rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 98 publications
2
42
0
Order By: Relevance
“…Since alcohol consumption and chronic viral infection are common risk factors for liver cancers ( 40 ), we analyzed if hepcidin downregulation had any additional effect on the patient’s survival. Hepcidin downregulation (HAMP low group) had a significantly worsening effect on overall and disease-specific survival in patients without alcohol consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Since alcohol consumption and chronic viral infection are common risk factors for liver cancers ( 40 ), we analyzed if hepcidin downregulation had any additional effect on the patient’s survival. Hepcidin downregulation (HAMP low group) had a significantly worsening effect on overall and disease-specific survival in patients without alcohol consumption.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the mutation frequencies of ZNF814, ZNF492, and ADAMTS12 were much lower in HCC tissues than in cfDNA. However, different gene mutations can be present based on the race or ethnicity of patients [ 21 ]. Therefore, the mutations of ZNF814, ZNF492, and ADAMTS12 might be important for HCC patients from Thailand specifically.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus, a component of the metabolic syndrome has been shown to attribute about 7% of the HCC cases worldwide (5,42). Meta-analyses have shown that diabetes is associated with HCC independent of viral hepatitis in which diabetic patients show 2-3 fold greater risks in developing HCC compared with non-diabetic controls (43).…”
Section: Metabolic Syndrome and Hccmentioning
confidence: 99%
“…Meta-analyses have shown that diabetes is associated with HCC independent of viral hepatitis in which diabetic patients show 2-3 fold greater risks in developing HCC compared with non-diabetic controls (43). The pathophysiological conditions such as hyperglycemia, hyperinsulinemia, insulin resistance, and activation of insulin-like growth factor signaling pathways provide a strong association for diabetes to be the risk factor in the pathogenesis of HCC (5,44). Obesity, a pathological state characterized by insulin resistance, hyperinsulinemia, and inflammation is also closely associated with HCC (45).…”
Section: Metabolic Syndrome and Hccmentioning
confidence: 99%
See 1 more Smart Citation